Multisectoral Analysis On The Awareness And Acceptability Of CSU Vision and Mission And College Of Teacher Education Goals and Program objectives - Escobar, Krizzette Joy C.; Belango, Manuel (International Journal of Arts, Sciences and Education, 2021)
The vision, mission, goals, and objectives (VMGO) of any institution serve as the cornerstone of an educational institution in realizing its thrusts, mandates as well as aspirations. With the objective to assess the level of awareness and level of acceptability of the vision and mission of Cagayan State University along with the College of Teacher Education goals and program objectives, this descriptive-inferential study was conducted. A total of 750 respondents, composed of students, parents, alumni, faculty and administration, and linkages and community served as study respondents. Data were gathered through a questionnaire and analyzed using mean and analysis of variance. It is evident from the results of the study that the different stakeholders are very much aware of the VMGO as a result of the various information and dissemination strategies utilized by the university. Likewise, the data also showed that the diverse sectors manifested a high level of acceptance of the VMGO due to their full participation in its formulation and the relevance of the objectives to the challenging demands of society. Furthermore, the findings indicated that the expressed level of awareness and level of acceptance of the different stakeholders on the VMGO did not differ. Key Words: Awareness, Acceptability, College of Teacher Education, CSU, Goals, Mission, Program Objectives, Vision,